The Buddhist ideal of bodhisattva. An historical outline of its ethical significance - Polo Santillán, Miguel Ángel (2022)
From the beginning of Buddhism, the figure of the bodhisattva appears, which, besides of being considered a stage prior to Buddhahood, became an ideal of realization open to anyone who wants to follow it. The bodhisattva is a complex ideal, since it encompasses different dimensions of human existence, such as the spiritual, intellectual, moral, psychological and religious. In this paper we want to present the value of this ideal, especially its ethical meaning, which has combined both theory and practice in those who have inspired their lives. We begin by looking at the etymology, the meanings in Theravada and Mahayana Buddhism, ending with the presentation of this ideal reviewing four contemporary Buddhist teachers. The relevance of this study is that this Buddhist ideal has brought to the Western mind a way of life full of meaning and because it can also be extended to the social commitments that individuals currently have.